Women's Employment, Children and Transition: An Empirical Analysis for Poland - Bardasi, Elena; Monfardini, Chiara (2012)
This article empirically investigates how the transition to a market economy affected the relationship between motherhood and labour force outcomes in Poland. We estimate different probit models on two panel datasets covering a three-year period before the reform (1987-1989) and a three-year period afterwards (1994-1996). Contrary to a priori expectations, our findings indicate that during transition young children were much less of a deterrent to the employment probability of their mother than they were before transition.